Implementation of Merdeka Belajar Curriculum at the Early Childhood Level in Insan Cemerlang Kindergarten Magetan - Irawati, Sutiyah Nova; Haidar, M (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
The Merdeka Belajar Curriculum is a government program in the education sector which aims to provide freedom and creativity to students, educators and educational units in developing their own and environmental potential. This curriculum also applies to early childhood (AUD), which is an important period for children's physical, cognitive, social and emotional development. This research aims to describe the implementation of the Merdeka Belajar curriculum at the AUD level at Insan Cemerlang Magetan Kindergarten. The research method used is a case study with a qualitative approach. Data was collected through observation, interviews and documentation. The research results show that Insan Cemerlang Kindergarten Magetan has implemented an Merdeka Belajar curriculum with several strategies, including: (1) developing a curriculum based on children's needs and interests; (2) using active, creative, effective and fun learning methods (PAKEM); (3) empowering the environment as a learning resource; (4) involving parents and the community in the learning process; and (5) carry out evaluations holistically and authentically. The implementation of the Merdeka Belajar curriculum at Insan Cemerlang Magetan Kindergarten has had a positive impact on the development of children's basic competencies, such as the ability to think critically, communicate, collaborate and have a positive attitude. The recommendation of this research is to improve coordination and supervision of the education department related to the implementation of the Merdeka Belajar curriculum at the AUD level.